2015
DOI: 10.1590/1982-0216201517415714
|View full text |Cite
|
Sign up to set email alerts
|

Estratégias de enfrentamento e perfil de participação e atividades vocais em professoras da rede pública de ensino com e sem distúrbios de voz

Abstract: Resumo:OBJETIVO:verificar a associação entre o distúrbio vocal com as características sociodemográficas, os aspectos vocais, os tipos de estratégias de enfrentamento e o impacto vocal nas atividades diárias em professoras da rede estadual de ensino de Alagoas.MÉTODOS:cento e dez professoras foram submetidas à análise perceptivo-auditiva, aos protocolos Condição de Produção Vocal do Professor, Protocolo de Estratégias de Enfrentamento das Disfonias e Perfil de Participação e Atividades Vocais. Por meio da Escal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 20 publications
0
8
0
1
Order By: Relevance
“…Por meio dos achados, pode-se observar que os estudos de correlação/associação são mais prevalentes [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] (19; 24,4%), seguidos daqueles que estudaram autopercepção 16,[34][35][36][37][38][39][40][41][42] (10; 12,8%) e sintomatologia 24,[43][44][45][46][47][48][49][50]…”
Section: Discussionunclassified
“…Por meio dos achados, pode-se observar que os estudos de correlação/associação são mais prevalentes [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] (19; 24,4%), seguidos daqueles que estudaram autopercepção 16,[34][35][36][37][38][39][40][41][42] (10; 12,8%) e sintomatologia 24,[43][44][45][46][47][48][49][50]…”
Section: Discussionunclassified
“…Studies about spoken voice show that the prevalence of some degree of dysphonia, assessed or self-reported in individuals who use their voice at work can reach 35,5% 29 , 43,3% 31 , 48% 7 , 50% 22,32 , 70% 33,34 , 80,7% 35 , 85% 26 e até 97,2% 36 , among others, a percentage higher than the 20% mentioned by colleagues.…”
mentioning
confidence: 83%
“…It is observed that many studies on spoken voice use these types of analyzes, which enables more effective discussion between the results of work 2,3,6,7,11,12,14,[19][20][21][22][23][24][25][26][27][28][29][30] . It should be noted also, the work published using the VOISS in dysphonic patients and presented, for example, its Table 1 19 (p.332) with the same kind of data structure and results of Tables 6, 7 and 8 1 (p.39-40), occurring even in Tables 1, 3 In addition to the balance sheet date and approval of the article 1 be earlier (mid-2013) to the validation of VoiSS 15 , on our analyzes about the means and frequency feature (described statistically) of our sample we didn't make inferences to the entire target population of future professional voice.…”
mentioning
confidence: 99%
“…The publication dates of the studies ranged from 2003-2017 spanning a period of 15 years. Of the seven included studies, three took place in the Netherlands, 18−20 two in Brazil, 21,22 one in Sweden 23 and one in Belgium. 14 Five studies employed a cross sectional study design with a control group, while the other two used a case control 23 and a longitudinal 20 study design.…”
Section: Study Characteristicsmentioning
confidence: 99%